On the systematics of the water mites Hygrobates nigromaculatus Lebert, 1879 and H. setosus Besseling, 1942 (Acari, Hydrachnidia, Hygrobatidae) - Tuzovskij, Petr V. (Zootaxa, 2017)
The first description of the deutonymph of the water mite Hygrobates setosus and a redescription of larvae, females and males of H. nigromaculatus and H. setosus are presented, with a comparative analysis of some morphological structures in all active stages of both species.